Japan : Financial System Stability Assessment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The Japanese financial sector remains weak notwithstanding a series of policy measures. The Financial System Stability Assessment assesses Japan's financial stability and structural changes in the deflationary, banking sector, life insurance, corporate sector, and the supervisory, transparency, and market integrity framework. It analyzes the macroeconomic development, policies, and financial system, and assesses the operations of government financial institutions and household sectors. It also reviews the assessment of the Basel core principle for effective banking supervision on the basis of the core principles methodology.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet